Komunikasi Efektif dalam Pengajaran Bahasa Inggris melalui Adaptasi Budaya Organisasi - Ridma Meltareza; Deni Hamdani (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The English language teaching at Pondok Pesantren Nurul Falah aims to improve the students' communication skills in English through an approach that is more adaptive to the organizational culture. This pesantren has a habit of using Arabic in daily life, so in the teaching of English, Arabic terms such as “huwa,” “huma,” and “huna” are used in teaching pronouns. The method applied involves interactive teaching, adapted to the students’ habits, where each session begins with an explanation of English concepts, which are then linked to Arabic terms that the students are already familiar with. This activity took place over four meetings per month, with morning and afternoon sessions. The results of the teaching activity showed an improvement in the students' understanding of basic English concepts, especially in teaching pronouns, which were easier to understand when linked to Arabic. The discussion in this activity revealed that adapting the language of instruction to the local culture, in this case, Arabic, can create a more comfortable atmosphere and support the students' enthusiasm for learning. Students, who initially felt less confident in speaking English, became more active and open to practicing. In conclusion, English teaching that is adapted to the organizational culture, especially through the use of Arabic in teaching, has proven effective in improving students' understanding and communication skills in English, as well as creating a learning environment that is more enjoyable and relevant to their needs